Developments in mineral carbonation for Carbon sequestration - Muhammad Imran Rashid; Zahida Yaqoob; M.A. Mujtaba; H. Fayaz; C Ahamed Saleel (Heliyon, 2023)
Mineral technology has attracted significant attention in recent decades. Mineral carbonation technology is being used for permanent sequestration of CO2 (greenhouse gas). Temperature programmed desorption studies showed interaction of CO2 with Mg indicating possibility of using natural feedstocks for mineral carbonation. Soaking is effective to increase yields of heat-activated materials. This review covers the latest developments in mineral carbonation technology. In this review, development in carbonation of natural minerals, effect of soaking on raw and heat-activated dunite, increasing reactivity of minerals, thermal activation, carbonations of waste materials, increasing efficiency of carbonation process and pilot plants on mineral carbonation are discussed. Developments in carbonation processes (single-stage carbonation, two-stage carbonation, acid dissolution, ph swing process) and pre-process and concurrent grinding are elaborated. This review also highlights future research required in mineral carbonation technology.